Intralobar pulmonary sequestration associated with Bochdalek hernia: first reported case in an adult male and literature review. Issue 8 (17th August 2018) - Lim, Daniel; Kostin, Raymond
Abstract: Pulmonary sequestrations (PS) are rare congenital malformations that can be difficult to diagnose. PS have no connection with the bronchial tree and are vascularized through an aberrant artery mostly arising from descending thoracic or abdominal aorta. The standard diagnostic method is the computed tomography angiography and delayed diagnosis can lead to recurrent pneumonia and hemoptysis. Herein, we have a case of a patient with an intralobar sequestration associated with a Bochdalek hernia. The diagnosis was delayed in this case as with many other similar case reports because details of the patient's history were overlooked.